Auditoría financiera en el rubro de ingresos del sector minero de Zaruma - Yépez Álvarez, Edgar Marcelo (2021)
The global environment demands the reasonableness of financial statements. In Ecuador, the mining sector is not exempt from compliance with the international framework for the presentation of financial reports, the purpose of which is to reflect the real situation of the companies; but unfortunately the companies dedicated to this sector show an insufficient accounting predilection with the International Financial Reporting Standards (IFRS) and International Accounting Standards (IAS). In the companies of the studied sector, the application of these standards is even a fundamental requirement to allow foreign investment in this type of companies, avoiding the implementation of IFRS 15 in particular, it would be like placing a barrier that would not allow companies to enter to new markets, expand and even lose space in the markets in which they are already working........